Maxillary Growth Evaluation Of Patients With Unilateral Complete Cleft Lip And Palate After Two Flap Palatoplasty With Honey Oral Drops - Kreshanti, Prasetyanugraheni; Handayani, Siti; Fortuna, Forry; Pancawati, Julieta; Susanto, Amila Jeni; Wangge, Grace; Indania, Alita (Jurnal Plastik Rekonstruksi, 2018)
Background : Honey given as oral drops significantly precipitate epithelialization of the lateral palatal defects post two-flap palatoplasty by 2.1 times. Honey is believed to reduce wound contraction, scar formation, and would contribute as an important factor that will result in a satisfactory maxillary growth. The aim of this study is to evaluate maxillary growth as the long-term effect of rapid epithelialization of the palates treated by honey oral drops. Method : This is a case control study consisting of 2 groups; comparing maxillary growth of the UCCLP patients that were and were not given honey as oral drops following their two-flap palatoplasty in 2011-2012. The cephalometric measurements were recorded and the dental cast are evaluated using GOSLON Yardstick method.Result : This study included a total of 20 patients. Goslon Yardstick type IV are the most frequent GOSLON on both groups (40%) with moderate inter-rater reliability between examiner 1-2 and 2-3 (kappa; 0.583 and 0.512) and substantial between examiner 1-3 (kappa 0.716). Forty-percent of SNA angle in the honey group were considered as normal, while only 20% normal SNA angle were found in the control group.Conclusion: Honey oral drops following two-flap palatoplasty resulted in satisfactory SNA angle. As the completion of maxillary growth occurs at the age of 20, the results of this study would only serve as a preliminary report. Other measures to support maxillary growth should also be taken into account. Further studies are warranted to discover innovations in surgical technique that may be a major contributing factor in maxillary growth. Keywords: Maxillary growth, Two Flap Palatoplasty, honey